Global weak solutions for a 2 × 2 balance non-symmetric system of Keyfitz-Kranzer type / Soluciones débiles globales para un sistema 2x2 balanceado no simétrico de tipo Keyfitz-Kranzer - Juajibioy Otero, Juan Carlos; De La Cruz Guerrero, Richard Alexander; Rendón Arbeláez, Leonardo (Universidad Pedagógica y Tecnológica de Colombia, 2017)
In this paper we consider the Cauchy problem for a particular non-symmetric Keyfitz-Kranzer type system,by using the vanishing viscosity method coupled with the compensated compactness method we get globalbounded entropy weak solutions. The main difficulty is to get uniformly bounded estimates on the viscositymethod.